My integrated writing companion / Xavier Thayalan … [et al.] - Thayalan, Xavier; Xavierine, Jane; Shanthi, Alice; Ismail, Zainon
My Integrated Writing Companion is a comprehensive guidebook for intermediate learners. The fundamental focus of this book is to help learners of English to write more effectively by developing specific writing skills. The book offers insights and step-by-step approach, beginning from sentence construction to paragraph building and then to essay writing. The sequential arrangement of the content in the book is able to assist beginners to become effective writers from relatively easy to difficult tasks. Besides focusing on developing sentences and paragraphs, My Integrated Writing Companion also integrates oral presentation and argumentative analytical skills. The book also integrates reading skills as a way to improve writing. This book is useful for students pursuing a writing course at the tertiary level and also for those preparing for the Malaysian University English Test (MUET).